Proportion and associated factors of the utilisation of complementary and alternative medicine exclusively in a hospital in Bangladesh - Md. Shahjalal; Jeff Gow; Md. Ashfikur Rahman; Md. Jakir Hossain; Md. Nafiul Alam Khan; Md. Sazzadul Alam; Ahmed Hossain; Rashidul Alam Mahumud (BMC, 2022)
Abstract Background Complementary and alternative medicine (CAM) has played a critical role in ensuring universal access to basic health care services around the world. In Bangladesh, conventional medicine is a common approach for health care practices, yet, due to Bangladesh's high out-of-pocket payment, millions of people utilise CAM-based healthcare services for illnesses. In Bangladesh, there is a scarcity of data on how CAM is perceived and utilised. The goal of this study was to determine the proportion and correlates of the utilisation of CAM among patients visiting a tertiary level hospital, in Bangladesh. Methods A cross-sectional survey involving 1,183 patients who received health care from a hospital in Bangladesh was interviewed for this study. The associated factors on utilising CAM were identified using multivariable logistic regression analysis. Results Thirty-three percent of patients utilised CAM exclusively to treat their illnesses, whereas the rest utilised conventional medicine before CAM. Young adult patients aged 26 to 45 years (AOR = 6.26, 95% CI:3.24-12.07), patients without education (AOR = 2.99, 1.81-4.93), and married patients (AOR = 1.79, 1.08-2.97) were the most likely to be only CAM users. The most common reasons for using CAM were belief in its effectiveness, less adverse effects, affordability and lower costs. Conclusion In Bangladesh, CAM plays a significant role in health care delivery, with high-levels of patient satisfaction and health benefits. Patients who are older and have a higher level of education are more hesitant to use CAM for their illness, yet CAM has the potential to play a significant role in reducing hospitalisation by providing high reliability and low costs.